Time to take HPV infection in colorectal cancer patients more seriously - Javadi, Mahsa; Jalilian, Shahram; Kanani, Malek; Kia, Vahid; Talaiezadeh, Abdolhassan; Angali, Kambiz Ahmadi; Ahmadi, Mohammad Karimi Baba; Makvandi, Manoochehr (Frontiers in Medicine, 2024)
Background The association between viral infections and colorectal cancer (CRC) remains an enigma in cancer research. Certain types of Human Papillomaviruses (hr-HPVs), known for their oncogenic properties, have been observed in particular CRC biopsies, further adding to the enigma surrounding this association. Materials and methods This cross-sectional study was conducted on 40 confirmed cases of CRC adenocarcinoma. The presence and genotyping of HPV DNA in colorectal fresh tissue and urine samples was assessed using an HPV DNA hybridization kit. A subset of serum samples from both CRC cases and healthy volunteers was randomly chosen and subjected to western blot to investigate the presence of HPV16 E6/E7 oncoproteins carried by exosomes. Results It was observed that 26/40 HPV-positive CRC patients demonstrated 7 times more chance to develop colorectal cancer when compared to those 8/40 normal tissue (odds ratio [OR] = 7.4; confidence interval [CI] 95% = 0.483156–0.793718; p < 0.001). Of 26 HPV-positive CRC patients, 14 urine samples were also showed HPV DNA positivity (p = 0.013). High-risk HPV16 was the most prevalent genotype detected in both 24/40 tumor and 12/40 urine samples (p < 0.001). The tumor sample of a male was HPV45, while another male’s urine sample was HPV31. A female CRC patient had HPV83 in tumor and HPV56 in urine. Here, was the first detection of HPV83 in a CRC patient. Notably among 20 randomly selected serum exosome samples, one serum sample concurrently tested positive for both HPV16 E6 and E7 oncoproteins, and one sample tested positive for HPV16 E7 oncoprotein. Conclusion High risk HPV DNA detection in CRC urine samples supports non-invasive screening tools. Detection of HPV16 E6 and E7 oncoproteins in exosomes from serum samples shows potential for non-invasive diagnostics. HPV’s potential role in CRC development is also underscored. HPV vaccination should be implemented in low- and middle-income countries to prevent cancer.